Forest growth and yield modeling - Weiskittel, Aaron R.; Hann, David W. (David William); Kershaw, John A., 1962-; Vanclay, Jerome K. (John Wiley & Sons, 2011)
Forest Growth and Yield Modeling synthesizes current scientific literature and provides insights in how models are constructed. Giving suggestions for future developments, and outlining keys for successful implementation of models the book provides a thorough and up-to-date, single source reference for students, researchers and practitioners requiring a current digest of research and methods in the field. The book describes current modelling approaches for predicting forest growth and yield and explores the components that comprise the various modelling approaches. It provides the reader with t.